2014
DOI: 10.1016/j.jmb.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Steroid Receptor RNA Activator Protein, the Proposed Partner of SRA Noncoding RNA

Abstract: In a widely accepted model, the steroid receptor RNA activator protein (SRA protein; SRAP) modulates the transcriptional regulatory activity of SRA RNA by binding a specific stem-loop of SRA. We first confirmed that SRAP is present in the nucleus as well as the cytoplasm of MCF-7 breast cancer cells, where it is expressed at the level of about 105 molecules/cell. However, our SRAP-RNA binding experiments, both in vitro with recombinant protein and in cultured cells with plasmid-expressed protein and RNA, did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…As such, the forementioned changes in gene expression are mostly very small. Interestingly, McKay et al concluded in their recent study, using a cut-off of two fold changes, that not a single gene appeared to be significantly regulated upon silencing SRA1 expression with individual siRNAs [25]. Our results corroborate their conclusion and suggest that SRAP does not act as a major transcriptional regulator.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As such, the forementioned changes in gene expression are mostly very small. Interestingly, McKay et al concluded in their recent study, using a cut-off of two fold changes, that not a single gene appeared to be significantly regulated upon silencing SRA1 expression with individual siRNAs [25]. Our results corroborate their conclusion and suggest that SRAP does not act as a major transcriptional regulator.…”
Section: Resultssupporting
confidence: 89%
“…This suggests that SRAP could be a potential prognostic marker and/or contribute to increasing tumor aggressiveness. Even though several groups have now tried to identify SRAP cellular functions, the exact roles played by this protein remain to be identified [5,21,22,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The SRA1 gene also encodes a protein steroid receptor coactivator protein (SRAP) (reviewed in (Leygue 2007)) that interacts with AR and is involved in PCa (Kawashima, et al 2003). Notably, SRA1 and SRAP do not interact (McKay, et al 2014). …”
Section: Mitochondrial-encoded Lncrnas and Lncrna Imported Into Mitocmentioning
confidence: 99%
“…A recent study reporting the crystal structure of human SRAP suggests that the protein does not harbor a predicted RNArecognition motif (RRM) but rather resembles the spliceosome complex protein PRP18 (also known as PRPF18) (McKay et al, 2014). Biochemical binding assays performed in vitro did not find a specific interaction between SRAP and SRA, nor was a specific response on estrogen receptor targets observed in cell culture assays.…”
Section: Steroid Receptor Activator Rnamentioning
confidence: 97%
“…Biochemical binding assays performed in vitro did not find a specific interaction between SRAP and SRA, nor was a specific response on estrogen receptor targets observed in cell culture assays. These observations have led to the proposal of an alternative model wherein SRAP is thought to stabilize intermolecular interactions within a nuclear splicing complex, rather than directly binding and regulating SRA RNA (McKay et al, 2014). Genetic analysis of the sra locus with mutations that disrupt specific SRA RNA versus SRAP domains, which could resolve the roles and mechanisms by which the RNA and protein function during development, differentiation and homeostasis, is currently lacking.…”
Section: Steroid Receptor Activator Rnamentioning
confidence: 99%